Challenges and solutions for application and wider adoption of wearable robots. (11th November 2021) - Babič, Jan; Laffranchi, Matteo; Tessari, Federico; Verstraten, Tom; Novak, Domen; Šarabon, Nejc; Ugurlu, Barkan; Peternel, Luka; Torricelli, Diego; Veneman, Jan F.
Abstract: The science and technology of wearable robots are steadily advancing, and the use of such robots in our everyday life appears to be within reach. Nevertheless, widespread adoption of wearable robots should not be taken for granted, especially since many recent attempts to bring them to real-life applications resulted in mixed outcomes. The aim of this article is to address the current challenges that are limiting the application and wider adoption of wearable robots that are typically worn over the human body. We categorized the challenges into mechanical layout, actuation, sensing, body interface, control, human–robot interfacing and coadaptation, and benchmarking. For each category, we discuss specific challenges and the rationale for why solving them is important, followed by an overview of relevant recent works. We conclude with an opinion that summarizes possible solutions that could contribute to the wider adoption of wearable robots.